INTENSIFIKASI PANGAN LOKAL SAGU DIKELURAHAN GURAPING. KECAMATAN OBA UTARA KOTA TIDORE KEPULAUAN - Johan Fahri; Musdar Muhammad (Bajang Institute, 2021)
This devotion aims to answer efforts to increase the production of cassava-made sago made by residents of Guraping village of North Oba Subdistrict. Community service using methods; Survey, observation, Focus Group Discussion (FGD) and Training and monitoring. The result of this devotion was carried out on August 26, on Thursday, 2021, when 20.00 Wit to completion, the participants who attended as many as 40 people and 29 people from the manufacture of cassava-based sago. the cultivation of the basic materials of cassava making for the long term, technological changes to increase production, in the form of replacing the scorching sun with a technological innovation, in the form of the latest accompaniment.jumalah the manufacture of cassava-based sago (kasbi) as many as 29 people, improving the quality of human resources and the need for institutions / cooperatives to manage, so that the increase of MSMEs in the community is increasing and there is an absorption of labor in the village, so that there is an economic increase in the income of the Guruping community